1985
DOI: 10.1002/jcp.1041220103
|View full text |Cite
|
Sign up to set email alerts
|

Release of hemopoietic factors by normal human T cell lines with either suppressor or helper activity

Abstract: We analyzed the release of activities capable of stimulating the in vitro growth of human hemopoietic progenitor cells by long-term cultured T cell growth factor (TCGF)-dependent human T lymphocytes. Seven cell lines tested produced colony-stimulating activity (CSA) as well as burst-promoting activity (BPA). The CSA stimulated primarily the growth of the cells forming colonies after 14 days of incubation. In addition the supernatants from these seven T-cell lines showed the ability to induce the in vitro growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The data are consistent with a previous report which suggested that murine leukemia virus could increase GM colony stimulating activity from murine fibroblasts (Koury and Pragnell, 1982). That multilineage hematopoietic factors may be produced by mitogen-stimulated human lymphocytes (Iscove et al, 1982), HTLV-infected lymphocytes (KoeMer et al, 1984), and lymphocyte cell lines not infected with retrovirus (Greenberger et al, 1984;Lanfrancone et al, 1985) is also consistent with this concept.…”
Section: Discussionsupporting
confidence: 92%
“…The data are consistent with a previous report which suggested that murine leukemia virus could increase GM colony stimulating activity from murine fibroblasts (Koury and Pragnell, 1982). That multilineage hematopoietic factors may be produced by mitogen-stimulated human lymphocytes (Iscove et al, 1982), HTLV-infected lymphocytes (KoeMer et al, 1984), and lymphocyte cell lines not infected with retrovirus (Greenberger et al, 1984;Lanfrancone et al, 1985) is also consistent with this concept.…”
Section: Discussionsupporting
confidence: 92%
“…GM‐CSF has a partial role in the eosinophil production [ 2]. On the other hand, T lymphocyte isolated from normal individuals do not have similar ability in vitro studies [ 1, 9, 10].…”
Section: Discussionmentioning
confidence: 99%